Little Bee Circuit As A Stimulation Aspect of Early Childhood Development - Esti Kurniawati Mahardika (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Games included into an integral part of early childhood learning methods. The present research was conducted to develop a game-based learning method for early childhood named ‘the little bee circuit’. This research implements research and development by Borg and Gall which consists of 10 steps. Furthermore, the little bee circuit game is designed sequentially and systematically so that it can stimulate five aspects of child development. The subjects in this study were teachers at five PAUD institutions and group B children in the Blitar Regency by the total respondents are 100. The data collection technique is the distribution of questionnaires to experts in the field of early childhood education, both from educators and early childhood education lecturers. The results of this study produced a learning program that is in accordance with the characteristics of early childhood and is believed to be able to stimulate 5 aspects of children growth and development